Evaluating Attendance Methods on IPB-Mobile for Student Application: A Case Study in IPB University - Putri, Najla Amelia; Rasendriya, Achmad Syahmi; Putri, Anatasya Wenita; Anggraeni, Aulia; Rabika, Jonathan Cristiano; Amin, Muhammad Al; Barus, Irma Rasita Gloria; Fami, Amata (Universitas Negeri Malang, 2023)
Currently, education is a crucial aspect of life. Technology has led to adaptations across various sectors, including higher education. One of these adaptations is the emergence of online attendance recording systems. IPB University has responded seriously to this by launching the IPB-Mobile for Student for Student app, which is equipped with a mobile-based self-attendance feature. Students can easily mark their attendance with just one click. However, this convenience is sometimes misused; one of the problems is students marking their attendance without attending classes. This issue has prompted a study into the effectiveness of the online attendance system in IPB-Mobile for Student for Student. Through the use of Short Versions of User Experience Questionnaires (UEQ-S) and interviews, it was found that the online attendance system is quite effective. Still, there is one aspect that makes this application quite complicated, thus requiring further updates